ASSESSMENT OF THE ATTITUDE OF HEALTH CARE PROFESSIONALS TOWARD PATIENT CONFIDENTIALITY AT UNIVERSITY OF PORT HARCOURT TEACHING HOSPITAL, RIVERS STATE, NIGERIA - Isaruk, Ikpoko-Ore-Ebirien Dike (Global Journal of Medical and Health Science, 2025)
Background: Protecting the privacy of patient information is essential for ethical health care, fostering trust between patients and providers. The rise of digital technology presents new challenges for maintaining confidentiality. The attitudes of health care workers greatly influence patient data safeguarding and adherence to ethical and legal standards. This study investigates the attitudes of health care professionals toward patient confidentiality at the University of Port Harcourt Teaching Hospital (UPTH) in Nigeria and primarily assesses health care workers’ knowledge of patient confidentiality policies, explores their attitudes toward maintaining confidentiality, and identifies factors influencing these attitudes at UPTH. Methods: A descriptive cross-sectional design was used. The study population included doctors, nurses, pharmacists, medical laboratory scientists, and health information management officers at UPTH. A stratified random sample of 300 health care workers was selected. Data were collected through structured questionnaires that assessed knowledge, attitudes, and influencing factors. Findings: Seventy percent of the respondents demonstrated adequate knowledge of confidentiality policies, with 76.7% being aware of the legal implications of breaches. Positive attitudes toward confidentiality were observed, with over 80% recognizing its importance for trust and hospital reputation. The results showed that training, institutional policies, and peer adherence strongly influenced attitudes, each of which affected 80% of the participants. Conclusion: Healthcare professionals at UPTH exhibit strong knowledge and positive attitudes regarding patient confidentiality. However, systemic challenges, such as workload and resource constraints affect consistent practice. The study recommends regular training workshops, incorporating confidentiality into professional curricula, and enhancing digital security to improve confidentiality practices in health care settings